Faktor yang Mempengaruhi Penyebab Kasus Anak ADHD dengan Metode Structural Equation Modelling Partial Least Square - Agusli, Fitri (Universitas Sultan Ageng Tirtayasa, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) sufferers are very high, namely 26.4% in Indonesia. This is supported by data from the 2007 Central Statistics Agency. Indonesia has 82 million children, of which one in five children and adolescents under the age of 18 have mental health problems, and at least 16 million children suffer from mental health problems, including ADHD. This disorder needs to be treated as early as possible to avoid more severe effects in adulthood and can affect a person's future if without immediate treatment. In order to reduce the incidence of ADHD children, especially in the city of Medan, researchers analyzed the factors that most influence cases of ADHD children using the Structural Equation Modeling (SEM) - Partial Least Square (PLS) method. SEM (Structural Equation Model) is a multivariate technique that will show how to represent a series or series of causal relationships in a path diagram. Furthermore, PLS is a variant-based SEM statistical method designed to complete multiple regression when specific problems occur in the data, such as small research sample sizes, missing data and multicollinearity. This research aims to find out what factors most influence the causes of cases of ADHD in Medan City using the Structural Equation Modeling (SEM) - Partial Least Square (PLS) method. Based on the results of the analysis in this study, it can be concluded that: genetic factors have an insignificant influence and a positive value of 0.417 on the characteristics of ADHD children, risk factors have an insignificant influence and a positive value of 0.260 on the characteristics of ADHD children, environmental factors have a significant influence not significant and has a positive value of 0.239 on the characteristics of ADHD children, the brain damage factor does not have a significant influence and has a negative value of -0.288 on the characteristics of ADHD children and the food additives and sugar factors have an insignificant influence and have a positive value of 0.371